2001
DOI: 10.1007/s002470100474
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile rheumatoid arthritis of the knee: evaluation with contrast-enhanced color Doppler ultrasound

Abstract: Contrast-enhanced color Doppler imaging holds promise for the detection of active synovial inflammatory disease in subclinical cases of JRA, thereby allowing earlier treatment and improved clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 0 publications
1
44
0
3
Order By: Relevance
“…They hold potential for detecting changes of low-volume, low-velocity blood flow in small vessels such as those of the synovium in arthritic joints [51].…”
Section: Microbubble Contrast-enhanced Ultrasonographymentioning
confidence: 99%
“…They hold potential for detecting changes of low-volume, low-velocity blood flow in small vessels such as those of the synovium in arthritic joints [51].…”
Section: Microbubble Contrast-enhanced Ultrasonographymentioning
confidence: 99%
“…Based on their researches on knee joint lesions of RA patients, Schmidt et al [22,23] found that the contrast-enhanced ultrasound could show blood perfusion of the synovium. Through the researches on adolescent RA, Doria et al [12,24] found that the ultrasound contrast can be applied to distinguish between active and non-active synovitis and to assess efficacy of treatment. The blood supply will be reduced after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of MRI and ultrasound to detect early, often subclinical disease by directly visualizing synovial inflammation is an advantage with regards to the prompt initiation of disease treatment [2,[9][10][11]. Both CT and fluoroscopy can also be used to guide for therapeutic interventions, as well as diagnostic procedures, such as myelography, providing additional dynamic and functional information.…”
Section: Discussionmentioning
confidence: 99%